A Comparative Study of in vitro Total Antioxidant Capacity, in vivo Antidiabetic and Antimicrobial Activity of Essential Oils from Leaves and Seeds of Zanthoxylum armatum DC. - Mehmood1, Ferhat; Aurangzeb2, Muhammad; Manzoor3, a; Fazal3, Sabiha (Asian Journal of Chemistry, 2013)
Zanthoxylum armatum DC. is a pharmaceutically important plant that has been claimed to be effective against various diseases in the folk medicinal system of Indian subcontinent. A detailed study regarding total antioxidant capacity (TAC) and radical scavenging, antidiabetic and antimicrobial effects of the essential oils from leaves (ZAL) and seeds (ZAS) of this plant were investigated. Essential oils obtained from steam distillation process were subjected to multiple assays. Total phenolic content values were found to be 28.46 and 29.90 mg/L gallic acid equivalent for ZAL and ZAS, respectively. A linear correlation was observed between the per cent inhibition of ABTS radical cation and the amount of essential oils with R2 = 0.996 and 0.997 for ZAL and ZAS, respectively. The per cent superoxide anion radical scavenging activity was found to be 44.75 and 45 % and reducing power in terms of FRAP values were 0.094 and 0.684 mM FeSO4 for ZAL and ZAS, respectively. All samples exhibited good metal chelating activities, the per cent inhibition of the complex formation was found to be 70.47 and 72.17 for ZAL and ZAS, respectively. None of the concentration of essential oils from different parts of Z. armatum showed any antidiabetic activity. The oils also showed antimicrobial and antifungal activities comparable to chloramphanicol. The data obtained from oils demonstrate the powerful antioxidative, radical scavenging and antimicrobial properties of the plant.